Habitual late sleep initiation is associated with increased incidence of type 2 diabetes mellitus in Korean adults: the Korean Genome and Epidemiology Study. Issue 7 (17th April 2019) - Seo, Ji A; Lee, Da Young; Yu, Ji Hee; Cho, Hyunjoo; Lee, Seung Ku; Suh, Sooyeon; Kim, Sin Gon; Choi, Kyung Mook; Baik, Sei Hyun; Shin, Chol; Kim, Nan Hee
Abstract: Study Objectives: Although sleep duration and quality were significant risk factors of type 2 diabetes (T2D), the impact of sleep initiation time on the development of T2D has not been studied in large longitudinal studies. Methods: A total of 3689 participants without diabetes aged 40–69 years at baseline were enrolled from the Korean Genome and Epidemiology Study and followed up for 12 years. Participants were categorized based on habitual sleep initiation time by questionnaire as follows: 20:00–22:59 (early sleepers, ES, n = 766), 23:00–00:59 (usual sleepers, US, n = 2407), and 1:00–5:59 (late sleepers, LS, n = 516). Incident T2D was identified biennially by fasting plasma glucose or 2-hour glucose after 75-g oral glucose loading or use of anti-diabetes medication. Results: During follow-up, 820 cases of T2D were documented and the LS group showed the highest increase in insulin resistance. Hazard ratio (HR) (95% confidence interval) for T2D of LS compared to ES was 1.34 (1.04–1.74) after adjustment for covariates including sleep duration. The impact of late sleep on the development of T2D was more evident in older individuals (≥65 years at baseline) (HR = 4.24 [1.42–12.68] in older LS vs. older ES, HR = 1.27 [1.00–1.62] in younger LS vs. younger ES, p interaction = 0.002). In addition, LS with low insulin secretion and sensitivity showed an approximately fivefold increased risk for T2D compared to ES with high insulin secretion and sensitivity. Conclusions/Interpretation: Habitual late sleep initiation is a significant risk factor for T2D in Koreans, especially in people with lower insulin sensitivity, lower β-cell function, and older age.